KEWAJIBAN PEMEGANG HAK MILIK ATAS TANAH UNTUK PENEMPATAN DAN PEMELIHARAAN TANDA-TANDA BATAS BIDANG TANAH DI DESA WAJOK HILIR KECAMATAN JONGKAT KABUPATEN MEMPAWAH - NIM. A1011181228, RAIZA RATU LUKMANA (Fakultas Hukum Universitas Tanjungpura, 2022)
Abstract Thelimited land parcels cause many land issues in the community so that they need to be controlled and there is a guarantee of legal certainty. To ensure legal certainty, land registration is necessary and the most important process is land measurement. Based on the provisions of Government Regulation Number 24 of 1997 concerning Land Registration, Article 17 paragraph (3) states that the placement of boundary signs, including their maintenance, must be carried out by the holder of the land rights concerned. However, there are still holders of land rights who have certificates but there is no placement and maintenance of land parcel boundaries and the majority of village communities still use boundary markings from plants, this causes disputes because these boundary markings are not permanent and if the plants are damaged or die then the boundary sign changes.The formulation of the problem in this research is